Uji Potensi Biogas dari Limbah Jeroan Ikan Patin (Pangasius sp.) dan Campuran Kiambang (Salvinia molesta) secara Anaerob Batch - Wahyu Kurniawan; Herpandi Herpandi; Susi Lestari (Jurnal FishtecH, 2016)
The purposed of this research to utilizing biomass of salvinia and viscera waste mixture of catfish as the biogas resource. The method of this research used experimental method at batch anaerob reactor and absortion carbon atom used NaCl and NaOH solution. The result of this research analysis used describtion method. The observed of parameter included rate analysis and accumulation of biogas production and metana, also parameter at slurry incuded temperature, pH, chemical oxygen demand, total solid, volatile solid and ratio C/N. The conclusion value of pH from this research between scale 1:2 (A1 reactor) and scale 1:1 (A2 reactor) is 7.9 and 7.15. COD in 5700 and 6400. C/N ratio in 5.19 and 5.96. The result indicated the different composition of subtrat slurry from salviana and vistera waste mixture of catfish in scale 1:2 (A1 reactor) produced biogas accumulation and metana the most than A2 reactor.